The Cervical Spinal Epiduritis, pertaining to Diagnosis, Treatment, and Outcomes: on severe spinal cord stenosis. A Case Report and a Literature Review: Cervical Spinal Epiduritis, pertaining to Diagnosis, Treatment, and Outcomes - Encarnacion-Santos, Daniel; Shestov, Eugeny; Pachev, Murat; Chmutin, Gennady; Chmutin, Egor; Rubenovich-Chikava, Dmitriy; Axenova, Marina; Chaurasia, Bipin (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2025)
Abstract Background: Osteomyelitis coupled with immunocompromised people with drug or intravenous drug use produces infective endocarditis. Remember that atlantoaxial subluxation accompanied by infection of the pharynx or nearby tissues is termed Grisel syndrome. [2]. Epidural abscesses are sometimes surgical emergencies, depending on the type of neurological impairments. An upper cervical epidural abscess in the occiput at the level of C2 is highly rare and uncommon. At the level of the subaxial spine at C3-C6 OR C7-T1 is the cervicothoracic area. Case Presentation A 54-year-old female patient reported experiencing cough and catarrhal symptoms for three months due to a previous coronavirus infection, accompanied by shortness of breath and joint pain. The patient's neck pain intensified, radiating to the left arm (myelopathy); conservative treatment was ineffective. MRI of the cervical spine indicated purulent spondyloarthritis affecting the left C4-C6 facet joints, with severe spinal cord stenosis (Figure 1), accompanied by epiduritis in the adjacent segment and abscess formation in the posterior paravertebral muscles of the neck. The surgical intervention consisted of a left C5-C6 hemilaminectomy with a microdiscectomy with which a metal cage was placed after sanitation and drainage of the purulent epiduritis, approach to the spondyloarthritis in the C4-C6 segments, and management of an intermuscular abscess with a cage. Conclusion Our clinical case shows a cervical spinal epiduritis with spinal cord stenosis, confirmed by imaging; therefore, once the diagnosis was confirmed, the decision was to perform an eminent surgical intervention with a hemilaminectomy and microdiscectomy.